Implementation of A* (A Star) Pathfinding Algorithm in 3D Isometric Projection Game “Survival Horror: Rabies Outbreak” - Ita Arfyanti; Muhammad Ibnu Saad; Leonardo Leonardo (TEPIAN, 2025)
Rabies remains a lethal zoonotic disease, claiming over 60,000 lives annually. Despite medical advancements, inadequate treatment and lack of awareness contribute to persistently high mortality rates. To enhance public education and engagement in rabies prevention, this study develops an educational game, “Survival Horror: Rabies Outbreak.” The game integrates a 3D isometric survival horror experience with real-world information on rabies transmission, prevention, and emergency responses. Players assume the role of a police officer delivering anti-rabies vaccines to infected residents while evading aggressive rabid animals. The game employs the A* (A Star) Pathfinding algorithm to enhance enemy AI, allowing dynamic and optimized pursuit behavior, thereby increasing realism and challenge. Beta testing with 10 respondents demonstrated that 60% of users rated the game positively, confirming its effectiveness as both an educational tool and an engaging survival-horror experience. The integration of AI-driven pathfinding with gamified learning provides a novel approach to public health education, offering an immersive method for raising awareness and fostering initiative-taking rabies prevention measures.